Kallikrein–Kinin System Suppresses Type I Interferon Responses: A Novel Pathway of Interferon Regulation - Seliga, Alecia; Lee, Michael Hweemoon; Fernandes, Nicole C.; Zuluaga-Ramirez, Viviana; Didukh, Marta; Persidsky, Yuri; Potula, Raghava; Gallucci, Stefania; Sriram, Uma (Frontiers in Immunology, 2018)
The Kallikrein-Kinin System (KKS), comprised of kallikreins (klks), bradykinins (BKs) angiotensin converting enzyme (ACE) and many other molecules, regulates a number of physiological processes, including inflammation, coagulation, angiogenesis and control of blood pressure. In this report, we show that KKS regulates Type I IFN responses, thought to be important in lupus pathogenesis. We used CpG (TLR9 ligand), R848 (TLR7 ligand) or recombinant IFN-α to induce Interferon Stimulated Genes (ISGs) and proteins, and observed that this response was markedly diminished by BKs, klk1 (tissue kallikrein) or captopril (an ACE inhibitor). BKs significantly decreased the ISGs induced by TLRs in vitro and in vivo (in normal and lupus-prone mice), and in human PBMCs, especially the induction of Irf7 gene (p<0.05), the master regulator of Type I IFNs. ISGs induced by IFN-α were also suppressed by the KKS. MHC Class I up regulation, a classic response to Type I IFNs, was reduced by BKs in murine dendritic cells (DCs). BKs decreased phosphorylation of STAT2 molecules that mediate IFN signaling. Among the secreted pro-inflammatory cytokines/chemokines analyzed (IL-6, IL12p70 and CXCL10), the strongest suppressive effect was on CXCL10, a highly Type I IFN-dependent cytokine, upon CpG stimulation, both in normal and lupus-prone DCs. Klks that break down into BKs, also suppressed CpG-induced ISGs in murine DCs. Captopril, a drug that inhibits ACE and increases BK, suppressed ISGs, both in mouse DCs and human PBMCs. The effects of BK were reversed with indomethacin (compound that inhibits production of PGE2), suggesting that BK suppression of IFN responses may be mediated via prostaglandins. These results highlight a novel regulatory mechanism in which members of the KKS control the type I IFN response and suggest a role for modulators of IFNs in the pathogenesis of lupus and interferonopathies.